A model to assess the importance of runway and taxiway particles to aircraft engine compressor deterioration - Scarso, Stefano; Staudacher, Stephan; Mathes, Jürgen; Schwarz, Norman (Frontiers in Mechanical Engineering, 2024)
During service, civil turbofans experience environmentally induced deterioration. Predicting this in a digital service twin model is computationally challenging due to the need to model both deterioration mechanisms and environmental conditions. For compressor erosion, a key challenge is to model particle ingestion throughout a flight mission (FM). During ground operations, these particles may be airborne or deposited on runways and taxiways. This work assesses the impact of the latter on turbofan core compressor deterioration during a mission. The airflow field in front of the engine intake is approximated using potential flow theory. Comparisons with measurements show that the predicted air velocity near the engine is underestimated since the inlet ground vortices generated from viscous effects are neglected. The forces acting on the particles are derived from the flow field. It turns out that most particles are lifted from the ground during take-off (TO). Yet only smaller particles below ≈ 50 µm are ingested into the engine intake. A deterioration model based on flat plate erosion experiments is used to compute mission severity, assuming all particles are similar to medium Arizona Road Dust. The results indicate that the engine’s distance from the ground, power setting, and the number of particles on the ground are key parameters influencing the impact of runway and taxiway particles. Considering the underestimation of the airflow field and thus the number of particles ingested, it is concluded that runway and taxiway particles play a major role in turbofan compressor deterioration.